High family SES and youth adjustment: The case of Chinese youth who were adopted from orphanages into American families. (March 2020) - Tan, Tony Xing; Yi, Zhiyao; Camras, Linda A.
Highlights: Adopted Chinese youth scored more favorably on BASC-3 than non-adopted Chinese youth. Adopted Chinese youth scored more favorably on BASC-3 than non-adopted US youth. High adoptive family SES benefited adopted youth adjustment. Testing measurement invariance is important for cross-cultural comparison. Abstract: In this paper, we examined if high SES families had an effect on youth's adjustment by comparing 226 internationally adopted female Chinese youth who experienced pre-adoption institutionalization with 1059 non-adopted Chinese peers living in China, as well as 209 non-adopted American peers. On average, the adopted youth's families had a higher SES status than the two comparison groups. Survey data on behavioral problems and prosocial adjustment were collected with the third edition of the Behavioral Assessment for Children (BASC-3). We found the adopted Chinese youth outperformed their Chinese counterparts in all comparisons and their US counterparts in most comparisons. These results offer some evidence that a high family SES may compensate for the adoption-related risks such as earlier institutionalization. Possible mechanisms underlying the benefit of high SES were discussed.